Cortisol, 11 beta-hydroxysteroid dehydrogenase type 1 and central obesity. - Stewart, P; Tomlinson, J (2002)
Observations on patients with Cushing's syndrome highlight the important role of glucocorticoids in regulating body fat distribution, specifically their link with central obesity. Circulating cortisol concentrations, however, are normal in the majority of patients with simple obesity. 'Pre-receptor' activation of cortisol from inactive cortisone by an enzyme 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1), expressed within adipose tissue itself, is emerging as a pivotal mechanism in regulating adipocyte differentiation. The development of specific 11β-HSD1 inhibitors might offer a novel approach to the treatment of central obesity. However 11β-HSD1 expression is reduced, not increased, in patients with obesity, and the enzyme is also expressed in adipose stromal cells where it might facilitate an antiproliferative effect of cortisol. The link between cortisol excess (be it endocrine or autocrine in origin) and central obesity is established, but further studies are required to define the real impact of 11β-HSD1.